Recent Trends in Group 9 Catalyzed C–H Borylation Reactions: Different Strategies To Control Site-, Regio-, and Stereoselectivity - Veth, Lukas; Grab, Hanusch A.; Dydio, Paweł (Synthesis, 2022)
Organoboron compounds continue contributing substantially to advances in organic chemistry with their increasing role as both synthetic intermediates and target compounds for medicinal chemistry. Particularly attractive methods for their synthesis are based on the direct borylation of C–H bonds of available starting materials since no additional pre-functionalization steps are required. However, due to the high abundance of C–H bonds with similar reactivity in organic molecules, synthetically useful C–H borylation protocols demand sophisticated strategies to achieve high regio- and stereoselectivity. For this purpose, selective transition-metal-based catalysts have been developed, with group 9 centered catalysts being among the most commonly utilized. Recently, a multitude of diverse strategies has been developed to push the boundaries of C–H borylation reactions with respect to their regio- and enantioselectivity. Herein, we provide an overview of approaches for the C–H borylation of arenes, alkenes, and alkanes based on group 9 centered catalysts with a focus on the recent literature. Lastly, an outlook is given to assess the future potential of the field.1 Introduction1.1 Mechanistic Considerations1.2 Selectivity Issues in C–H Borylation1.3 Different Modes of Action Employing Directing Group Strategies in C–H Borylation1.4 Scope and Aim of this Short Review2 Trends in C–H Borylation Reactions2.1 Photoinduced Catalysis2.2 Transfer C–H Borylation2.3 Lewis Acid Mediated C–H Borylation2.4 Directed Metalation2.5 Miscellaneous C–H Borylation Reactions2.6 Electrostatic Interactions2.7 Hydrogen Bonding3 Conclusion and Outlook
Keywords: catalysis; borylation; C–H functionalization; iridium; rhodium; cobalt